A necklace of water - Tiernan, Cate (Tiernan, Cate. Balefire, 2006)
As the consequences of the Treize's magickal rite become more fully known, twin witches Clio and Thais pursue separate agendas involving Daedalus, and Melita returns with plans of her own.